1994
DOI: 10.1038/370111a0
|View full text |Cite
|
Sign up to set email alerts
|

Folding of nascent polypeptide chains in a high molecular mass assembly with molecular chaperones

Abstract: The folding of polypeptides emerging from ribosomes was analysed in a mammalian translation system using firefly luciferase as a model protein. The growing polypeptide interacts with a specific set of molecular chaperones, including Hsp70, the DnaJ homologue Hsp40 and the chaperonin TRiC. The ordered assembly of these components on the nascent chain forms a high molecular mass complex that allows the cotranslational formation of protein domains and the completion of folding once the chain is released from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
488
4
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 629 publications
(530 citation statements)
references
References 48 publications
32
488
4
6
Order By: Relevance
“…The folding function of HSPs relates to their capacity to recognize the hydrophobic amino acid chains exposed by non native proteins, whereas the actual folding by the different HSPs occurs in various ways. HSP70 folds nascent polypeptides and releases them via con formational changes by HSP90 in the cytoplasm, with HSP60 assisting in the final folding of proteins in an enclosed cage 35,36 . The folding machinery is assisted by the small HSPs, which function as 'holdases' involv ing binding to unfolded proteins and assisting in their delivery to the 'foldases' (REFS 4,37).…”
Section: The Proteostasis Network Componentsmentioning
confidence: 99%
“…The folding function of HSPs relates to their capacity to recognize the hydrophobic amino acid chains exposed by non native proteins, whereas the actual folding by the different HSPs occurs in various ways. HSP70 folds nascent polypeptides and releases them via con formational changes by HSP90 in the cytoplasm, with HSP60 assisting in the final folding of proteins in an enclosed cage 35,36 . The folding machinery is assisted by the small HSPs, which function as 'holdases' involv ing binding to unfolded proteins and assisting in their delivery to the 'foldases' (REFS 4,37).…”
Section: The Proteostasis Network Componentsmentioning
confidence: 99%
“…Further, upon deletion of TF, the polypeptide flux through DnaK increases from ~ 15% to ~ 40% showing that there is partial functional redundancy between different classes of chaperones (Teter et al, 1999). Using firefly luciferase as a model protein, it was shown in rabbit reticulocyte lysate (RRL) that Hsc70 together with Hsp40 and TRiC sequentially mediate the folding of luciferase nascent chains and depletion of either of these chaperones disrupts the highly organized chaperone pathway (Frydman et al, 1994). In S. cerevisiae, it was shown that Hsp70 and TRiC cooperate in the folding and assembly of the Von Hippel-Lindau (VHL) tumor suppressor complex (Melville et al, 2003).…”
Section: Ii41121 the Hsp70 Chaperone Systemmentioning
confidence: 99%
“…TRiC, like GroEL, is an essential protein since at least two cytoskeletal proteins, actin and tubulin, are obligate substrates of TRiC (Dobrzynski et al, 1996;Gao et al, 1992;Llorca et al, 1999;Yaffe et al, 1992). Unlike GroEL/ES which can act only post-translationally, TRiC has been shown to fold the discrete domains of firefly luciferase co-translationally (Frydman et al, 1994). From biochemical studies using unfolded firefly luciferase, actin and tubulin, it has been shown that while GroEL/ES failed to fold these model proteins, TRiC was able to mediate their folding, suggesting that it can interact with a different range of substrates via mechanism distinct from class I chaperonins (Frydman et al, 1992;Tian et al, 1995;Yam et al, 2008).…”
Section: Ii4113 the Chaperoninsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the eukaryotic cytosol, both genetic and biochemical evidence support interaction of Hsp70 class proteins with nascent polypeptide chains (Beckmann et al, 1990;Nelson et al. 1992;Frydman et al. 1994).…”
Section: A Pat-ollel Nent-ork Of Chaperones Binding P O L P~p T I D mentioning
confidence: 99%